Integrated approach for the optimal design of pipeline networks - Ayad, A.; Awad, H.; Yassin, A. (Alexandria engineering journal, 2018)
This paper presents the development of a GIS-based model for water pipeline network data integration and analysis named Integrated Water Distribution network design and Calibration Utility (IWDCU). IWDCU tackles two main applications in the field of Water Distribution Network (WDN). The first application (ELGTnet) addresses hydraulic analysis for both looped and branched networks. Also, based on Evolutionary Algorithms (EAs), EAnet is a computer-based technique for the optimal hydraulic design of WDN that satisfies both design demands and pressures at all network nodes with lowest possible cost. For the abovementioned two computer applications, mathematical modeling was combined with Geographic Information System (GIS) application for better data visualization and for best performance. The application of this integrated approach was subsequently further tested in Kostol Irrigational area to evaluate its applicability to real applications and its performances in finding best commercial design of network.